2001
DOI: 10.1007/bf02981939
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myelogenous Leukemia WithPIG-A Gene Mutation Evolved from Aplastic Anemia—Paroxysmal Nocturnal Hemoglobinuria Syndrome

Abstract: We report a patient with aplastic anemia (AA)-paroxysmal nocturnal hemoglobinuria (PNH) syndrome who developed acute myelogenous leukemia (AML). Flow cytometric analysis showed that the leukemic cells in the bone marrow lacked CD59 antigen on their surface and were positive for P-glycoprotein. Heteroduplex and single-strand conformation polymorphism analysis followed by sequencing of the leukemic cells in the bone marrow disclosed 1 frameshift-type mutation in exon 2 of the phosphatidylinositol glycan-class A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Haematopoietic stem cells that are defective in GPI anchor assembly owing to a mutation in the PIGA gene preferentially expand in the bone marrow and give rise to defective peripheral blood elements that are deficient in GPI-anchored protein expression. Mutation in the X-linked PIGA gene causes paroxysmal nocturnal haemoglobinuria, a disease characterized by haemolytic anaemia, thrombosis and impaired bone marrow function, with an increased risk of developing leukaemia 211 . tumour mass through electrostatic repulsion of negative charges, which physically inhibits and disrupts cell-cell adhesion 114,115 .…”
Section: Box 1 | the Unique Type Of Notch Glycosylationmentioning
confidence: 99%
“…Haematopoietic stem cells that are defective in GPI anchor assembly owing to a mutation in the PIGA gene preferentially expand in the bone marrow and give rise to defective peripheral blood elements that are deficient in GPI-anchored protein expression. Mutation in the X-linked PIGA gene causes paroxysmal nocturnal haemoglobinuria, a disease characterized by haemolytic anaemia, thrombosis and impaired bone marrow function, with an increased risk of developing leukaemia 211 . tumour mass through electrostatic repulsion of negative charges, which physically inhibits and disrupts cell-cell adhesion 114,115 .…”
Section: Box 1 | the Unique Type Of Notch Glycosylationmentioning
confidence: 99%
“…For genotyping of the CYP3A5*3 allele and CYP3A4*1G allele, we used the polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) method 21 The CYP2D6*5 (deleted) allele and CYP2D6*10 (reduced) allele were identified using long PCR analysis and the PCR-RFLP method, respectively, as described by Naveen et al 22 Genotyping procedures identifying the C and T alleles in exon 12 (1236C > T), the G and T/A alleles in exon 21 (2677G>T/A), and the C and T alleles in exon 26 (3435C>T) of the ABCB1 gene were performed using the PCR-RFLP method described by Wu et al, 23 Tanaka et al, 24 and Cascorbi et al, 25 respectively. The ABCG2 421C>A polymorphism was genotyped using the PCR-RFLP method of Kobayashi et al 26 The analytic results obtained from PCR-RFLP were confirmed using a fully automated SNP detection system (prototype i-densy; ARKRAY Inc, Kyoto, Japan).…”
Section: Genotype Identificationmentioning
confidence: 99%
“…CYP3A5*3 (6986A4G (rs776746)) and SLC22A1 (156T4C (rs1867351), 480G4C (rs683369), 1022C4T (rs2282143) and 1222A4G (rs628031)) genotyping was performed by PCR-RFLP, as previously described by Fukuen et al 34 and Itoda et al, 25 respectively. Similarly, ABCC2 (À24C4T (rs717620)) and ABCB1 (1236T4C (rs1128503), 2677G4T/A (rs2032582) and 3435T4C (rs1045642)) were genotyped as described by Naesens et al, 35 Wu et al, 36 Tanaka et al 37 and Cascorbi et al, 38 respectively. ABCG2 421C4A (rs2231142) was genotyped as described by Kobayashi et al, 39 and SLCO1B3 (334T4G (rs4149117)) as described by Tsujimoto et al 40 All genotype frequencies were tested for Hardy-Weinberg equilibrium.…”
Section: Measurement Of Plasma Im Concentrationmentioning
confidence: 99%